Experimental Study of Flow over the Triangular Side Weir with Inclined Crest in Subcritical Flow - M. Neisi; M. Sajadi; M. Shafai Bejestan; J. Ahadiyan (علوم آب و خاک)
Side weirs are hydraulic structures employed in irrigation and drainage channels as diversion devices or head regulators. The increasing efficiency of the structure of side weirs for constant head has been one of the concerns of researchers in the last decade. The use of different forms of sharp crest, labyrinth, piano key, and increasing the length of the overflow by changing the geometry of the crest have been investigated. In this research, a new type of triangular-shaped side weir has been studied in the laboratory under different hydraulic conditions in sub-critical flow conditions. The results demonstrated that by inclining the crests of the triangular side weir, the amount of vortex created at the entrance of the opening was reduced. So the discharge coefficient and the flow volume over the side weir showed an increase of up to 27% and 48%, respectively, compared to the normal triangular and rectangular side weirs. Also, after analyzing the data, a non-linear equation was presented to estimate the discharge coefficient with the dimensionless parameters of the ratio of the upstream depth to the weir height (y1/p) and the upstream Froud number (Fr1) with an accuracy of ±15% and NRMSE=0.134.